Analisis Psikologi Sastra Kumpulan Cerpen Bunga Tabur Terakhir Karya G.M. Sudarta - Yastuti, Ryan Dwi (Humanis; Volume 4. No. 2. Agustus 2013, 2013)
The objective of this study is the main character in cluster of short stories entitled Bunga Tabur Terakhir written by G.M. Sudarta, himself is a caricaturist. Background of this study is because the short story has a unique characteristic created by a famous and talented caricaturist. Beside that, Bunga Tabur Terakhir is enriched with the psychological aspects makes it is suitable to analyze using the psychological literature. In the psychological analysis theory of personality structure proposed by Sigmund Freud which are id, ego, and superego is used and the defense mechanism. Those three components are affected behavior, pattern of thinking and psychology of the main characters. From the analysis it can be found that the main characters have the strong id. They tend to avoid the uncomfortable feeling ignoring the reality that they actually can not do that. The defense mechanism is found in four short stories in Bunga Tabur Terakhir , although it is not usually success.
Keywords: Bunga Tabur Terakhir, psychologycal literature, personality structure